Performance of Broilers on Dietary Supplementation of Black Cumin (Nigella sativa) Seed During Monsoon Season - Devi, N. Sushma; Vidyarthi, V. K.; Zuyie, R. (International Journal of Bio-resource and Stress Management, 2022)
The present research work was conducted with the aim to find out the effect of black cumin seed feeding on the growth, feed efficiency, blood profile and economics of broiler production during summer season. For this, a total of 120 Cobb-400 strains of broilers were selected and subjected to four dietary treatments with 30 birds each having five replications per treatment. The birds of control group were offered standard broiler starter diet till 21 days and thereafter standard finisher diet up to 42 days. The birds of other groups were also offered the same diet as in control groupalong with black cumin seed powder supplementation at the rate of 1.0, 2.0 and 3.0% of the diet. In monsoon season, feed intake and feed conversion efficiency was significantly (p<0.05) higher in2% and the poorest in1% black cumin supplemented group. Black cumin seed had significant (p<0.05) effect on WBC, RBC, PCV and HDL.The haematological and biochemical parameters were found to have positive effect in the treatment groups as compared to control group. However, the control group had the highest net profit return as compared to the treatment groups at which positive effect of black cumin seed was not achieved in terms of economics. Hence, it was concluded that using of black cumin seed as herbal feed additive helps in the improvement of health condition of the birds.